Mathematical description of the asynchronous two-machine aggregate with a rotating inductor - Lutsio, V. V.; Silvestrov, A. M.; Boryak, B. R. (Видавництво Львівської політехніки, 2018)
It was developed mathematical description of the asynchronous two-machine aggregate with a rotating inductor, that was made as an initial stage of development of its full-fledged simulation model. The use of this class of electric machines is relevant in high-speed electric drives, without using frequency converter or raising gearbox, as well as the ability to distribute different speed motion on two shafts.
Keywords: asynchronous machine; two-machine aggregate; mathematical description; rotating inductor; 621.313